(untitled) (Medico Legal Update, 2021)
Introduction: Diabetic foot syndrome (DFS), a complex disorder, affects diabetics. It is the unique anatomy of the foot that leads to potentially serious infection. Three cardinal aetiological factors that predispose to diabetic foot ulcers are ischaemia, neuropathy and infection. DFUs are challenging to cure as often the diagnosis is delayed; there is presence of ischaemia, infection with multidrug-resistant organism and extension of infection to the bones. This study was conducted with the aim to determine the clinical and microbiological profile of diabetic foot patients and to assess their outcome. Methodology: Sixty five male and female patients of 18 and above age that presented with diabetic foot ulcers were enrolled over a period of 18 months. Results: Of the 65 patients enrolled, 70.77% (n=46) were males while 29.23% (n=19) were females. Male to female ratio was 2.4:1. Diabetic foot ulcers are common in elderly population. Most commonly seen in the age group of 51 to 60 years. When we evaluated the Wagner grade of the ulcers, it was observed that majority of the patients had Wagner grade III ulcer (44.62%) followed by grade II ulcer in 24.62% of the patients. None of the patients enrolled in the present study had wagner grade I ulcer. When the risk factors presence was evaluated in the patients, 63.08% patient had suffered trauma, this was followed by peripheral neuropathy which was present in 60.00% patients. Among the patient enrolled, 36.92% were smokers. 63.08% patients had diabetes for more than 10years while 20% had diabetes of 5-10 years duration and only 16.92% patients had diabetes of less than 5 years. We observed that USG showed presence peripheral vascular disease in 41.54% patients, which is considerably high. In the present study X-ray showed presence of Charcot’s joint, osteomyelitis, fracture and osteoporosis in 10.77%, 24.62%, 3.08% and 4.62% patients respectively. We observed that in our study, anemia was present in large proportion of patients, 67.69%, in the present study. In the present study, ulcer was managed conservatively in 38.46% of the patients. I & D was performed in 35.38% of the patients. While amputation was performed in 12.31% of the patients. In the present study, the following organisms were isolated: Staphylococcus aureus, Pseudomonas Aeruginosa, Klebsiella pneumonia, Streptococcus pyogenes and Proteus Mirabilis were present in 36.92%, 9.23%, 13.85%, 18.46% and 10.77% patients, respectively. Thus the most common isolate was Staphylococcus aureus followed by Klebsiella pneumonia. We observed that 50% staphylococcus aureus isolates were resistant to methicillin, that is methicillin resistant staphylococcus aureus. However, the isolated staphylococcus did not demonstrate resistance to vancomycin or linezolid. Gram negative organisms showed no resistance to Piperacillin+tazobactum,Imipenem and Meropenem in the present study. Amputation was performed in all the patients with Wagner grade IV and V ulcers, while it occurred in 48.15% patients with vasculopathy and 33.33% patients with neuropathy. It was also observed that in those patients with proteus infection, amputation had to be performed in 100% patients. Conclusion: Diabetic foot ulcers pose a significant burden on the patients and on the health care system. The cost of disability, loss of work and lower extremity amputation extends beyond the economic impact, with regards to patient quality of life. Proper management of diabetic infections requires appropriate antibiotic selection based on culture and antimicrobial susceptibility results; however, initial management comprises empirical antimicrobial therapy, which is often based on susceptibility data extrapolated from studies performed on general clinical isolates.